The use of the silver sulfadiazine 1% in colpitis treatment - Ferrari, Renato (2002)
Introduction: The vaginitis are caused by a series of infectious agents and are the principal reason for the gynecological consultation. They are very common around the world and affect women in all social classes. There are plenty of treatments. But there is not a drug efficient in all cases. Objectives: To study the use of Silver Sulfadiazine 1%, as a vaginal cream, in the treatment of vaginitis caused by different agents. Methods: Its a pilot study, non comparative, using adult alphabetized women with vaginitis, who attended a public health service (Hospital Universitário Clementino Fraga Filho) and private office. The Silver Sulfadiazine 1% vaginal cream was used in the vagina for 6 consecutive days (Ginodermazine ). Results: There was studied 35 cases of vulvo-vaginal candidiasis. 5 cases of trichomoniasis, 26 cases of bacterial vaginosis and 10 cases of unspecific vaginitis. The results were satisfactory. All cases of trichomoniasis and unspecific vaginitis were treated successfully, but only two cases of candidiasis and also two cases of bacterial vaginosis showed therapeutic failure. Conclusion: As there were low number of collateral effects and high grade of cure of vaginitis of different etiologies, a vaginal cream of Silver Sulfadiazine 1% must be considered as a new therapeutic option.